2015
DOI: 10.4238/2015.august.19.15
|View full text |Cite
|
Sign up to set email alerts
|

Association between the XRCC1 Arg399Gln polymorphism and risk of cervical carcinoma: a meta-analysis

Abstract: ABSTRACT. Numerous studies have evaluated the association be tween Arg399Gln polymorphism of DNA repair gene XRCC1 and cervical carcinoma risk. However, the spe cific association is still controversial. To assess the relationship between XRCC1 Arg399Gln polymorphism and cervical carcinoma, we conducted a comprehensive meta-analysis of 10 case-control studies with 2051 cervical carcinoma cases and 2919 controls. Meta-analysis results based on all the studies showed a significant association between XRCC1 Arg399… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A latest meta-analysis exploring the association between the Arg399Gln polymorphism and cervical cancer showed that the Arg399Gln polymorphism increased the risk of cervical cancer [27]. The result contradicted ours and the reasons may include the following.…”
Section: Discussionmentioning
confidence: 68%
“…A latest meta-analysis exploring the association between the Arg399Gln polymorphism and cervical cancer showed that the Arg399Gln polymorphism increased the risk of cervical cancer [27]. The result contradicted ours and the reasons may include the following.…”
Section: Discussionmentioning
confidence: 68%
“…A comprehensive meta-analysis of 10 case-control studies gathering 2051 CC cases and 2919 control subjects showed a significant association with no ethnic differences between white and Asian populations. 37 These findings were further confirmed in Chinese population where a significantly elevated risk was observed. 38 Our results are in agreement with these findings and provide independent confirmation cohort in our population.…”
Section: Discussionmentioning
confidence: 63%
“…24,25 However, little published information is available regarding the association between polymorphism of XRCC1, XRCC2 and XRCC3 gene and susceptibility to cervical carcinoma. 26 Also, few studies from Northern and Southern India have reported the genetic polymorphisms in the DNA repair genes with respect to a variety of cancer risks including prostate, breast, oral and esophageal cancers, but only couple of studies available to reveal the association of polymorphisms in XRCC1, XRCC2 and XRCC3 genes with CC development and the results were with incompatible conclusions. 27,28 Some recent studies discovered positive association of Arg194Trp variant of XRCC1 with CC development risk while other demonstrated a strong association of the Arg399Gln polymorphism with an increased risk of CC, but other failed to find the significant result.…”
Section: Discussionmentioning
confidence: 99%